Examining the drivers of changes in stripping ratio in open pit coal mining: a system dynamics model to optimize the coal discrepancy - Oktovianus Bakkula; Dermawan Wibisono; Manahan Siallagan (Discover Applied Sciences)
Abstract Stripping ratio (SR), as one of the critical parameters in coal mining, refers to the ratio of overburden (OB) or waste removed to obtain a ton of coal. It influences the coal discrepancy, or the difference between actual and planned coal mined production. This study aims to explore the contributing factors to the change in SR. The author carried out a focus group discussion (FGD) involving experts at one of the largest coal mining companies in Indonesia. Empirical data collected from January to December 2024 verified the results related to the causes of changes in SR. The output variables from the data collecting analysis are utilized for modeling this phenomenon using Vensim PLE 7.3.5, a system dynamics (SD) software, to assess the influence of all contributing factors. The study revealed that the geological model and pit optimization positively decrease the SR. On the other hand, changes in sequence, redesigning the pit, operational loss, failure, and rehandling activity have an opposite impact on SR. Based on the simulation at model X, the best scenario is G (with the contributing factor of a coal increase of 15% from the original), which has an average SR of 6.26 and a total coal mined production of 1,626,018.1 tonnes at t = 1932. Simulation of model Y revealed that scenario G7 has the highest total coal mined production of 1,604,088.8 tonnes, with the average SR at 6.34. However, scenario G4 shows the highest revenue of $130,712,149.0 as well as a profit of $85,327,620.9.